THE EFFECT OF PROBLEM BASED LEARNING APPROACH AND PLAYING METHOD AND NUTRITIONAL STATUS ON MOTOR ABILITY OF STATE ELEMENTARY SCHOOL - Visano, Diski; Gusril, Gusril; Syahara, Sayuti; Putra, Aldo Naza; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
The problem in this study is the lack of motor skills. This study aims to determine the effect of problem based learning and playing methods and nutritional status on motor skills of Elementary School 12 Mandau, Bengkalis RegencyThis study uses an experimental method that uses a treatment design with a level of two x two, namely a factory experiment involving two factors. The sample in this study were 20 students of Elementary School 2 Mandau. Nutritional status data were taken by means of tests and measurements using the Body Mass Index (BMI) instrument and to measure motor ability tests using the "Scott Motor Ability" test instrument.Data were analyzed using 2 x 2 ANOVA at a significance level of α = 0.05 and the Kolmogorov-Smirnov sig normality test> 0.05 and continued with the Tukey test. The results of the data analysis show that 1) Overall, Problem Based Learning is better than the Play Method in improving motor skills of Elementary School 12 Mandau, Bengkalis Regency. 2) There is an interaction between Problem Based Learning and Play Method with Nutritional Status on the results of motor skills of Elementary School 12 Mandau, Bengkalis Regency. 3) In the High Nutritional Status Group, Problem Based Learning and high nutritional status are better and more influential than the play method group with high nutritional status on the motor skills of Elementary School 12 Mandau, Bengkalis Regency. 4) In the Low Nutritional Status Group, Problem Based Learning and low nutritional status are better and more influential than the play method group with low nutritional status on the motor skills of Elementary School 12 Mandau, Bengkalis Regency.